226k views
0 votes

h(x) = x -1 + \frac{1+ ln {}^(2) (x) }{x}


\displaystyle \lim_(x\to0) h(x)= \: ? \\ \displaystyle \lim_(x\to \infty ) h(x)= \: ?
Apply L'Hôpital's Rule if possible​

1 Answer

4 votes

Answer:


\lim_(x\rightarrow +\infty ) x-1+(1+ln^(2)x)/(x) = + \infty


\lim_(x\rightarrow 0 ) x-1+(1+ln^(2)x)/(x) = + \infty

Explanation:


\lim_(x\rightarrow +\infty ) x-1+(1+ln^(2)x)/(x)


= [\lim_(x\rightarrow +\infty ) (x-1)]+[ \lim_(x\rightarrow +\infty ) ((1+ln^(2)x)/(x))]

= +∞ + 0

= +∞


\lim_(x\rightarrow +\infty ) x-1+(1+ln^(2)x)/(x)


= [\lim_(x\rightarrow 0 ) (x-1)]+[ \lim_(x\rightarrow 0 ) ((1+ln^(2)x)/(x))]

= -1 + +∞

= +∞

h(x) = x -1 + \frac{1+ ln {}^(2) (x) }{x} \displaystyle \lim_(x\to0) h(x)= \: ? \\ \displaystyle-example-1
User Anthoney
by
4.4k points